2016
DOI: 10.1353/cpr.2016.0046
|View full text |Cite
|
Sign up to set email alerts
|

House Chats as a Grassroots Engagement Methodology in Community-Based Participatory Research: The WE Project, Petersburg

Abstract: Background The Wellness Engagement Project is an academic-community partnership developed to engage the community to inform the development of a pilot intervention aimed at promoting healthy eating and physical activity among residents of Petersburg, Virginia. Objectives To implement House Chats as a novel methodology for engaging community members in focused discussion about obesity, exercise, dietary intake, and barriers to health. Methods We recruited and trained laypersons as House Chat Leaders to host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The partnership conducted an extensive needs assessment to understand the community's perceptions and challenges related to managing a healthy lifestyle. We used diverse research methods including asset mapping (Mosavel et al, 2018), house chats (Mosavel et al, 2016), focus groups, key informant interviews, and a community survey (Mosavel et al, 2020), which resulted in the development and pilot testing of a peer-led, community-based intervention to increase physical activity and nutrient-rich foods (LaRose et al, 2021). Ethics approval was received from the Virginia Commonwealth University institutional review board for all aspects of the research (HM14742).…”
Section: Academic-community Partnershipmentioning
confidence: 99%
“…The partnership conducted an extensive needs assessment to understand the community's perceptions and challenges related to managing a healthy lifestyle. We used diverse research methods including asset mapping (Mosavel et al, 2018), house chats (Mosavel et al, 2016), focus groups, key informant interviews, and a community survey (Mosavel et al, 2020), which resulted in the development and pilot testing of a peer-led, community-based intervention to increase physical activity and nutrient-rich foods (LaRose et al, 2021). Ethics approval was received from the Virginia Commonwealth University institutional review board for all aspects of the research (HM14742).…”
Section: Academic-community Partnershipmentioning
confidence: 99%
“…As a first step to developing a community-based intervention, a needs assessment was conducted by the research team, which included the WA. A total of six focus groups were held with representatives from community and faith-based organizations, businesses, the health sector, parents and youth; 34 House Chats (focused conversations led by a community member in a home setting) were conducted with 181 participants (Mosavel et al, 2016), 40 key informant interviews were completed, a community survey was conducted (N = 1,317), and an asset-mapping project was completed by teams of Petersburg youth and university students who identified 358 different assets in Petersburg (Mosavel et al, 2018). The data collected during this phase confirmed that obesity was a major health concern for many Petersburg residents and also shed light on the unique social and environmental barriers residents experienced.…”
Section: Background and Community Contextmentioning
confidence: 99%
“…The script was based on key findings and themes identified from the WE Project formative research which included family-based change, community cohesion, acknowledgment of social determinants of health, and motivational skills for changing unhealthy behaviors. Additionally, the team, which included the researchers, community members in the role of WAs, and CHLC members, determined that it would be important to address the numerous barriers to healthy living identified in the formative research including the perception that a healthy lifestyle is expensive or what "well-off" people do, that healthy living takes too much time, that healthy eating is seen as "punishment," and that there is a lack of knowledge of how to cook "healthy" (Mosavel et al, 2016). These key findings and themes were provided to the Conciliation Project and were intertwined with relevant statistics and data about health and obesity to inform the script for the play.…”
Section: Using Theater Arts As Data Dissemination: Changes and Choicementioning
confidence: 99%
See 1 more Smart Citation
“…We can learn from cancer survivor models of engaging the survivor as educator (Saad-Harfouche et al 2011) and train those with experience in tissue donation: family members who have lost a loved one and donated to a biobank are often highly motivated to share their experiences and to provide personal testimonies. Creative and personalized methods such as house chats (members of social circle disseminating information) (Mosavel et al 2016) and reaching-in to community at places where they typically gather (churches, etc.) (Campbell et al 2007;Linnan et al 2014) and directly inviting community members to share their concerns can maintain the momentum of the initial education program.…”
Section: Iscussionmentioning
confidence: 99%